Transcriptional, Posttranscriptional, and Posttranslational Regulation of SHOOT MERISTEMLESS Gene Expression in Arabidopsis Determines Gene Function in the Shoot Apex . Issue 2 (18th December 2014) - Aguilar-Martínez, José Antonio; Uchida, Naoyuki; Townsley, Brad; West, Donnelly Ann; Yanez, Andrea; Lynn, Nafeesa; Kimura, Seisuke; Sinha, Neelima
Abstract : A homeobox gene key for plant development is regulated at the transcriptional, posttranscriptional, and posttranslational levels. Abstract: The activity of SHOOT MERISTEMLESS ( STM ) is required for the functioning of the shoot apical meristem (SAM ). STM is expressed in the SAM but is down-regulated at the site of leaf initiation. STM is also required for the formation of compound leaves. However, how the activity of STM is regulated at the transcriptional, posttranscriptional, and posttranslational levels is poorly understood. We previously found two conserved noncoding sequences in the promoters of STM -like genes across angiosperms, the K-box and the RB-box. Here, we characterize the function of the RB-box in Arabidopsis ( Arabidopsis thaliana ). The RB-box, along with the K-box, regulates the expression of STM in leaf sinuses, which are areas on the leaf blade with meristematic potential. The RB-box also contributes to restrict STM expression to the SAM . We identified FAR1-RELATED SEQUENCES-RELATED FACTOR1 (FRF1) as a binding factor to the RB-box region. FRF1 is an uncharacterized member of a subfamily of four truncated proteins related to the FAR1-RELATED SEQUENCES factors. Internal deletion analysis of the STM promoter identified a region required to repress the expression of STM in hypocotyls. Expression of STM in leaf primordia under the control of the JAGGED promoter produced plants with partially undifferentiated leaves. We further found that the ELK domain has a role in the posttranslational regulation of STM by affecting the nuclear localization of STM.